The Principle of Judicial Independence in the Context of the Evolution of EU Law - Jarukaitis, Irmantas; Morkūnaitė, Monika (Teisė, 2021)
This article examines the significance and the content of the principle of judicial independence and its assurance based on Article 267 of the Treaty on the Functioning of the European Union and Article 19 (1) of the Treaty on European Union. The interaction between these provisions is analysed in the context of the development of the case-law of the Court of Justice of the European Union.
Keywords: Jurisdiction of the Court of Justice; rule of law; requirement of judicial independence; references for a preliminary ruling; Article 267 TFEU; Second subparagraph of Article 19(1) TEU